The influence of online review videos on gross anatomy course performance among doctor of chiropractic students - Zipay, Nicole M. (J Chiropr Educ, 2019)
OBJECTIVE: Technology-enhanced learning is on the rise within healthcare education. This pilot study evaluated the relationship between the use of online review videos and students' performance and satisfaction in gross anatomy. METHODS: For this quasi-experimental study, we developed a series of online gross anatomy review videos, and surveyed students enrolled in a doctor of chiropractic program regarding use of the videos and their attitudes towards using the videos. Ordinal regression was used to evaluate the relationship between students' video use and course performance and the Mann-Whitney U test was used to determine whether there was a difference in course performance between students who did and did not report using the review videos. RESULTS: We received 143 responses to our survey, resulting in a 73.3% response rate. Most students (71%) had engaged with the online review videos. No significant differences in course performance were detected between students who did and did not report using the videos. Many students (82%) reported the review videos as being “helpful” and 73% perceived them as “an enjoyable way to study.” CONCLUSION: While chiropractic students perceived a series of online gross anatomy review videos as being an enjoyable and helpful way to study, engagement with this form of technology-enhanced learning did not have an impact on their overall gross anatomy course performance.